Numerical Simulations of a Bubble Growth and Departure on the Horizontal Wall Using Thermal Lattice Boltzmann Method. (June 2015) - Wei, Yikun; Feng, Kongfang; Li, Qifei
The process of bubble nucleation, growth and detachment are simulated using thermal lattice Boltzmann method. As the bubble grows to a certain size, it will eventually detach from an active nucleation site especially for the case of a pool boiling of a horizontal wall. Numerical results are compared qualitatively with the experimental results. A qualitative agreement is reached. It can also be concluded that the departure diameter decreases as the wall superheat decreases, while the growing time increases. It is has been ascertained that both growing time and departure diameter increase as gravity decreases.